Modulation of Macrophage Polarization by Viruses: Turning Off/On Host Antiviral Responses - Yu, Shaoxiong; Ge, Hailiang; Li, Su; Qiu, Hua-Ji (Frontiers in Microbiology, 2022)
Macrophages are professional antigen-presenting cells and serve as the first line of defense against invading pathogens. Macrophages are polarized towards the proinflammatory classical (M1) or anti-inflammatory alternative (M2) phenotype upon viral infections. M1-polarized macrophages exert critical roles in antiviral responses via different mechanisms. Within the long competitive history between viruses and hosts, viruses have evolved various immune evasion strategies, inhibiting macrophage acquisition of an antiviral phenotype, impairing the antiviral responses of activated macrophages, and/or exploiting macrophage phenotypes for efficient replication. This review focuses on the sophisticated regulation of macrophage polarization utilized by viruses and is expected to provide systematic insights into the regulatory mechanisms of macrophage polarization by viruses and further facilitate the design of therapeutic targets for antivirals.